Response Modeling of Integrated Security Systems - Zilys, M.; Valinevicius, A. (Elektronika ir Elektrotechnika, 2000)
Here is described response modeling of integrated security system. Estimation of security reaction is among the most important application for system and is one of the critical requirements for ISS.